Study of double-tagged gamma gamma events at LEPII - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2006)
Double-tagged interactions of photons with virtualities Q2 between 10 GeV2 and 200 GeV2 are studied with the data collected by DELPHI at LEPII from 1998 to 2000, corresponding to an integrated luminosity of 550 pb-1. The γ*γ* → μ+μ- data agree with QED predictions. The cross-section of the reaction γ*γ* → hadrons is measured and compared to the LO and NLO BFKL calculations.